Pengembangan LKPD Menulis Teks Deskripsi Berbasis Nilai-Nilai Karakter Peserta Didik SMP Kelas VII - Heriza Nevisi Yanda Putri; Mulyanto Widodo; Siti Samhati (Universitas Lampung, 2020)
This study aims (1) to produce LKPD products writing description text based on character values, (2) Describe the feasibility of LKPD writing description text based on character values developed based on the assessment of material experts, media experts, practitioners, teachers and students. This study adapted research and development (RD) by Borg and Gall. The character value in this LKPD, the value of the main character that is sourced from the PPK Pancasila. This research was conducted in three schools including SMPN 3 Katibung, MTs Nur El Ihsan Katibung, and MTs. GUPPI 1 Babatan Katibung. The results of this study indicate that (1) has produced